VECTORS OF TURKISH FOREIGN POLICY: WHAT REMAINS OF THE STRATEGY FOR 2023? - Slobodan Janković (Međunarodni Problemi)
The article examines the probability of achieving the self-imposed criteria for Turkey to become a macro-regional power by 2023. The author analyses components of variables in Davutoğluʼs equation of power and the results of the “zero problems with neighbours” policy as an essential prerequisite for Turkey becoming one of the poles of power at the global level. Presenting the state of progress in military industries, in the development of technological infrastructure and in the economy, the author assesses the limited progress and failure to materialise the country’s expected goals. After years of progress in various fields, the leading AKP party is now troubled by conflicts inside and outside the country. The author concludes that Turkey will not be able to realise its 2023 strategy due to combination of failures in internal, foreign and economic policies.